Data on selfـــefficacy and its sources during the COVID-19 crisis: A Saudi auditor’s perspective [version 2; peer review: 1 approved, 2 approved with reservations] - Ali Ali Al-Ansi; Saeed Rabea Baatwah; Mahfoudh Hussein Mgammal (F1000Research)
Background Auditors during COVID-19 experienced an unprecedented situation, in which normal audit activities were difficult to conduct. Moreover, COVID-19 forced auditors to introduce a new audit approach, “remote auditing,” which was not common in most audit firms and required the adoption of more advanced technologies. Overall, auditors during the COVID-19 pandemic needed both cognitive and technical factors to deliver high-quality audits. Despite these challenges, research on how auditors deal with these issues is limited, presenting an intriguing area of study. Methods This dataset provides insights into Saudi auditors’ experience and beliefs regarding audit activities during COVID-19. Through an online survey, researchers collected data from 193 of 417 registered auditors with the Saudi Organization for Chartered and Professional Accountants (SOCPA). The survey assessed auditors’ self-efficacy in conducting audits during the pandemic and explored its sources and potential moderating factors. Specifically, the dataset includes responses to eight items related to self-efficacy, 19 items covering four common sources of self-efficacy (mastery experience, vicarious experience, social persuasion, and physiological/emotional states), and six items assessing virtual audit competency. Additionally, the dataset contains demographic information that is valuable for researchers analyzing the relationship between auditor self-efficacy, its sources, and other influencing factors. Conclusions Overall, the dataset included in this study may serve a broader audience and be useful in improving several stakeholders’ understanding of the effects of COVID-19 on auditors and how auditors assess their ability to adapt to COVID-19 consequences. This study contributes to the existing body of knowledge by highlighting the need for auditors to adapt to new circumstances and adopt innovative approaches during challenging times, thereby ensuring the delivery of high-quality audits.